Abundance and taxonomic data of spiders collected with pitfall traps from temperate forest stands from Lower Saxony, Germany in 2019 - Dragan Matevski (PANGAEA, 2022)
Abundance and taxonomic data of spiders (family, genus and species) collected with pitfall traps from temperate forest stands from Lower Saxony, Germany. Five forest stand types were studied (Douglas fir monoculture, European beech/Douglas fir mixture, European beech monoculture, European beech/Norway spruce mixture, Norway spruce monoculture) at seven different sites, four in southern (site 1-4) and three (5,7,8) in northern Lower Saxony, Germany. Eight pitfall traps were set at each of the 35 plots and the material was collected every three weeks starting from 03.09.2019.
In: Matevski, Dragan; Kriegel, Peter (2022): Abundance and taxonomic data of arthropods collected with pitfall traps from temperate forest stands from Lower Saxony, Germany in 2019 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.949484